Comparative Efficacy of High-Dose versus Low-Dose Bleomycin–Lipiodol Transarterial Chemoembolization in Adult Hepatic Hemangiomas: A Retrospective Cohort Analysis - Muhammad Ramzan, Abdullah Saeed, Khoala Riaz, Asim Ali, Muhammad Usman Younas, Fazal Ullah (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Hepatic hemangiomas are the most common benign liver tumors and are usually detected incidentally; however, symptomatic or large lesions often require intervention. Surgical resection, while effective, is associated with substantial morbidity, prompting increasing use of minimally invasive therapies such as transarterial chemoembolization (TACE) with bleomycin. Objective: To compare hemangioma response patterns reported in previous low-dose bleomycin interventions with outcomes observed in a cohort treated with high-dose (45 IU) transarterial bleomycin–Lipiodol TACE. Methodology: This retrospective cohort study was conducted in 31 adult patients with hepatic hemangiomas at Pakistan Kidney and Liver Institute and Research Centre - PKLI, Lahore from January 2022 to December 2022. Hemangioma response was evaluated following single-session or limited-session transarterial chemoembolization using a cumulative bleomycin dose of 45 IU emulsified with Lipiodol. Radiological assessment was performed using contrast-enhanced CT or MRI, with standardized three-dimensional volumetric measurements. Results: Technical success was achieved in all patients, with satisfactory intralesional Lipiodol deposition observed in 74%. No patient developed post-embolization syndrome. Only one patient (3%) developed a liver abscess, which was managed conservatively. Follow-up imaging was available for 26 patients, demonstrating a mean volumetric reduction of 71.4%. Clinical success (≥50% lesion regression) was achieved in 88% of patients, with 50% exhibiting ≥80% volumetric regression after a single treatment session. Only two patients (6%) required repeat embolization. Conclusion: Compared with previously reported low-dose protocols, high-dose bleomycin–Lipiodol TACE demonstrated superior single-session efficacy, a markedly reduced need for repeat interventions, shorter hospitalization, and an excellent safety profile. These findings support high-dose TACE as a safe, effective, and durable minimally invasive treatment option for hepatic hemangiomas. Keywords: Hepatic hemangioma; Bleomycin–Lipiodol; Transarterial chemoembolization; High-dose bleomycin; Radiological outcomes; Minimally invasive therapy